Apprentissage coopératif ou pédagogies coopératives ? - Sylvain Connac; Albert Irigoyen (Éducation et Socialisation)
Many pedagogies and pedagogical practices recommend the use of cooperative organizations of student work. This orientation towards greater sociality is motivated by the educational project of contributing to the success and well-being of everyone. However, the traditions in this area are old and different cultures have emerged. This theoretical article attempts to bring together two conceptions of school cooperation: cooperative learning (apprentissage coopératif) and cooperative pedagogies (pédagogies coopératives). While the first rather prioritizes the development of cooperative skills, to learn to cooperate, the second comes in various forms through devices that mostly seek to have students learn by cooperating. In addition to real structural differences, these approaches appear both rigorously thought out and complementary to think about the place of relationships in pedagogy.